Effect of low-dose lidocaine on objective upper extremity strength and immediate pain relief following cervical interlaminar epidural injections: a double-blinded randomized controlled trial. Issue 10 (11th October 2020) - McCormick, Zachary L.; Burnham, Taylor; Cunningham, Shellie; Kendall, Richard W; Bougie, David; Teramoto, Masaru; Walega, David R.
Abstract : Background: Low-dose lidocaine is a common diluent for analgesia following cervical interlaminar epidural steroid injection (CIESI). Concerns with this practice exist. A single-arm cohort reported that 20% of patients develop postprocedural upper extremity weakness when using lidocaine as a diluent. Furthermore, a high-cervical spinal block with unintended intrathecal or subdural administration is possible. Objective: Determine if low-dose lidocaine as a diluent during CIESI causes clinically meaningful (1) upper extremity weakness and (2) immediate pain relief when compared with saline. Design: Double-blinded randomized control trial. Methods: Patients with cervical radicular pain scheduled for CIESI were enrolled. Participants received lidocaine (CIESI-L) or saline (CIESI-S) as a diluent for the epidural injectate. Myotomal strength was measured with dynamometry before and between 20 and 30 min after CIESI. Pre-pain and post-pain scores were obtained. Primary and secondary outcomes were post-CIESI weakness of ≥20% (minimal clinically important difference (MCID)) in > 1 myotome and ≥50% pain reduction on the numerical scale. Results: 120 participants (64 females (53%), mean age, 56 (SD 13.7) years) completed the study and were analyzed (CIESI-L n=60; CIESI-S n=60). There was no significant between-group difference in the proportion of participants with postprocedural weakness, CIESI-L 41.7% (95% CI, 29.8% to 54.5%), CIESL-S 50% (95% CI, 37.5% to 62.5%). Between-group comparison showed no significant difference in pain reduction, relative risk 1.53 (95% CI, 0.82 to 2.86). Conclusion: Low-dose lidocaine as a diluent in CIESI does not significantly increase the risk of post-CIESI myotomal weakness when compared with saline, but also does not substantially increase the likelihood of immediate, meaningful pain relief. Trial registration details: ClinicalTrials.gov (NCT03127137 ); December 26, 2017.